The impact of surgery and radiotherapy on health-related quality of life of individuals with oral and oropharyngeal carcinoma and short-term follow up after treatment - Goiato, Marcelo Coelho [UNESP]; Amoroso, Andressa Paschoal [UNESP]; Silva, Bruna [UNESP]; dos Santos, Emerson Gomes; de Caxias, Fernanda Pereira [UNESP]; Bitencourt, Sandro Basso [UNESP]; Moreno, Amália; dos Santos, Daniela Micheline [UNESP] (EpiSmart Science Vector, 2020)
Objective: This study aimed to evaluate the quality of life of patients with oral or oropharyngeal cancer by using specific questionnaires (QLQ-C30 and QLQ-HandN35), varying according to the location of the tumor (oral cavity or oropharynx) and the treatment performed (only surgery or surgery associated with radiotherapy). Methods: Fifty patients were enrolled in this study and answered the EORTC QLQ-C30 and EORTC HandN35 questionnaires, before (baseline), at 1 week, and 3 months after treatment. Internal consistency reliability was calculated with the Cronbach coefficient. The Kruskal-Wallis and Wilcoxon tests were applied and P<.05 was considered significant. Results: Some aspects showed significant difference (P<.05) between tumor location (oral/oropharyngeal) and treatment performed (surgery or surgery plus radiotherapy) only for the baseline and 1 week after treatment periods. Conclusion: Quality of life is a factor that affected patients with head and neck cancer. The time elapsed after treatment, whether surgical or surgical plus radiotherapy, influenced patient quality of life. The period of greatest morbidity was 1 week after treatment.
Keywords: Mouth neoplasms; Oropharyngeal neoplasms; Quality of life; Radiotherapy; Surgical oncology